Legal–Fiscal Integration in PPP Models for Sustainable Financing of Free Nutritional Meal Programs - Iwan Kusnawirawan; Yofi Syarkani; Hernayati; Dwi Ratna Sari Handayani; Muhammad Arsyad Subu; Imam Waluyo (Indonesian Scientific Publication, 2026)
The expansion of Free Nutritional Meal Programs (FNMPs) has intensified fiscal and governance challenges, particularly in countries operating under constrained public budgets and evolving regulatory frameworks. While Public–Private Partnerships (PPPs) are increasingly promoted as alternative financing mechanisms, existing studies tend to treat legal and fiscal dimensions separately, creating a critical gap in understanding how integrated governance design supports sustainability.This study examines how PPP models can be leveraged through a legal–fiscal integration framework to ensure sustainable FNMP financing. Using a qualitative document-based policy analysis, the research systematically reviews academic literature from Scopus and Web of Science, combined with policy and evaluation reports from institutions such as the World Bank and OECD. A total of 48 documents were analyzed using thematic coding and an evidence-linkage matrix to ensure transparency and analytical rigor. The findings identify three interdependent governance mechanisms: hybrid financing structures, performance-based payment systems, and adaptive risk allocation frameworks. These mechanisms collectively demonstrate that sustainability in FNMP-oriented PPPs is not determined by single policy instruments, but by the integration of legal enforceability and fiscal design.This study contributes by developing an integrated legal–fiscal governance framework for nutrition-focused PPPs, offering a novel policy perspective that bridges public finance and legal design. The framework provides actionable guidance for policymakers to transform politically driven nutrition programs into fiscally sustainable and institutionally robust public health systems.